Oligodendrocyte and Extracellular Matrix Contributions to Central Nervous System Motor Function: Implications for Dystonia. Issue 3 (6th January 2022) - Yellajoshyula, Dhananjay; Pappas, Samuel S.; Dauer, William T.
Abstract: The quest to elucidate nervous system function and dysfunction in disease has focused largely on neurons and neural circuits. However, fundamental aspects of nervous system development, function, and plasticity are regulated by nonneuronal elements, including glial cells and the extracellular matrix (ECM). The rapid rise of genomics and neuroimaging techniques in recent decades has highlighted neuronal–glial interactions and ECM as a key component of nervous system development, plasticity, and function. Abnormalities of neuronal–glial interactions have been understudied but are increasingly recognized to play a key role in many neurodevelopmental disorders. In this report, we consider the role of myelination and the ECM in the development and function of central nervous system motor circuits and the neurodevelopmental disease dystonia. © 2022 International Parkinson and Movement Disorder Society